Early Experience with a Novel Cannulation Strategy for Left Ventricular Decompression during Nonpostcardiotomy Venoarterial ECMO. Issue 3 (May 2016) - Keenan, Jeffrey E.; Schechter, Matthew A.; Bonadonna, Desiree K.; Bartz, Raquel R.; Milano, Carmelo A.; Schroder, Jacob N.; Daneshmand, Mani A.
Abstract : Advances in technology for the delivery of venoarterial extracorporeal membrane oxygenation (VA-ECMO) have allowed for its expanded utilization in the treatment of patients with advanced cardiogenic shock, particularly through the use of peripheral cannulation strategies. However, peripheral VA-ECMO continues to be hampered by several major limitations including inadequate decompression of the left ventricle, lower limb ischemia, and the inability to mobilize patients. Here, we present a case series of three patients who were treated with a hybrid peripheral-central cannulation strategy accompanied by direct decompression of the left ventricle through a right anterior mini-thoracotomy. This novel approach ameliorates several of the current limitations to peripheral VA-ECMO therapy and thereby holds potential for improving outcomes in VA-ECMO patients.